MMP-9 Downregulation with Lipid Nanoparticles for Inhibiting Corneal Neovascularization by Gene Silencing - Torrecilla, Josune (Nanomaterials (Basel), 2019)
Gene silencing targeting proangiogenic factors have been shown to be a useful strategy in the treatment of corneal neovascularization (CNV). Among interference RNA (RNAi) molecules, short-hairpin RNA (shRNA) is a plasmid-coded RNA able to down-regulate the expression of the desired gene. It is continuously produced in the host cell, inducing a durable gene silencing effect. The aim of this work was to develop a solid lipid nanoparticle (SLN)-based shRNA delivery system to downregulate metalloproteinase 9 (MMP-9), a proangiogenic factor, in corneal cells for the treatment of CNV associated with inflammation. The nanovectors were prepared using a solvent emulsification-evaporation technique, and after physicochemical evaluation, they were evaluated in different culture cell models. Transfection efficacy, cell internalization, cell viability, the effect on MMP-9 expression, and cell migration were evaluated in human corneal epithelial cells (HCE-2). The inhibition of tube formation using human umbilical vein endothelial cells (HUVEC) was also assayed. The non-viral vectors based on SLN were able to downregulate the MMP-9 expression in HCE-2 cells via gene silencing, and, consequently, to inhibit cell migration and tube formation. These results demonstrate the potential of lipid nanoparticles as gene delivery systems for the treatment of CNV-associated inflammation by RNAi technology.